THE PECULIARITIES OF INITIATING A CRIMINAL CASE ON CRIMES RELATED TO EXTREMIST ACTIVITY - Nurumbetova Sadokat Allayarovna, (International Journal of Innovations in Engineering Research and Technology, 2023)
The article covers the subject matter, the circumstances to be determined, the evidence and their significant aspects, until the investigation into the application and complaints received in criminal cases related to extremism. The specifics of the issue of initiating or rejecting a criminal case are expressed based on the circumstances on which the case is based.